The Production Administrative Structure: A Paradigm for Strategic Fit - Jelinek, Mariann; Burstein, Michael C. (Academy of Management Review, 1982)
This paper presents the manufacturing production management system as an administrative structure intimately and interactively fitted into the context of the firm. Drawing on the literatures of organization theory and strategy, a contingent-theoretic view is posed, suggesting that the production administrative structure (PAS), along with its administrative context, must maintain a dynamic fit with the evolving strategy and environment of the firm.